Solid-state electrolyte, preparation method of solid-state electrolyte and solid-state battery

CN122907715APending Publication Date: 2026-10-13GUIZHOU HANGSHENG LITHIUM ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611262343.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,纯PDOL电解质在室温下的离子电导率很低,且其电化学稳定窗口较窄,难以满足高电压正极材料的使用需求;同时,PDOL基体对锂盐阴离子的固定能力不足,导致锂离子迁移数偏低(通常低于0.5),浓差极化显著,锂金属负极表面电场分布不均,进而诱发锂枝晶生长

Benefits of technology

[0021]与现有技术相比,本公开的有益效果是:本公开制备得到了一种具有良好的离子电导率以及提高固态电池循环保持率的固态电解质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907715A_ABST
    Figure CN122907715A_ABST
Patent Text Reader

Abstract

The present disclosure relates to the field of solid-state electrolyte, in particular to a solid-state electrolyte, a preparation method of the solid-state electrolyte and a solid-state battery. The solid-state electrolyte comprises the following components by weight: 65-85 parts by weight of poly(1,3-dioxolane) polymer matrix, 12-25 parts by weight of lithium salt, 0.2-2 parts by weight of first metal organic framework filler, 0.2-2 parts by weight of inorganic solid-state electrolyte particles, 0-3 parts by weight of inorganic additive and 0-5 parts by weight of organic additive; wherein the inorganic solid-state electrolyte particles are selected from one or more of lithium lanthanum zirconium tantalum oxide (LLZTO), lithium aluminum titanium phosphate (LATP) and lithium lanthanum titanium oxide (LLTO).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of solid electrolytes, specifically to a solid electrolyte, a method for preparing a solid electrolyte, and a solid battery. Background Technology

[0002] With the rapid development of electric vehicles and large-scale energy storage systems, the market demand for high-energy-density and high-safety rechargeable batteries is becoming increasingly urgent. Lithium metal anodes, with a theoretical specific capacity as high as 3860 mAh / g and the lowest electrochemical potential (-3.04 V vs. SHE), are considered the anode choice for next-generation high-energy-density battery systems. However, traditional liquid electrolytes have extremely poor compatibility with lithium metal. The uncontrolled growth of lithium dendrites during cycling not only leads to rapid capacity decay but also poses a significant safety hazard of puncturing the separator and causing internal short circuits. Therefore, replacing liquid electrolytes with solid-state electrolytes and constructing solid-state lithium metal batteries is considered a key path to overcome these bottlenecks.

[0003] Among various solid electrolytes, solid polymer electrolytes have attracted much attention due to their excellent flexibility, processability, and electrode interface adhesion. Poly(1,3-dioxolane) (PDOL), prepared through in-situ ring-opening polymerization of 1,3-dioxolane (DOL) monomers, can fully wet electrode pores as a liquid precursor during battery assembly, subsequently transforming into a solid polymer in situ, thus fundamentally solving the interfacial contact problem between solid electrolytes and electrodes. However, pure PDOL electrolytes have very low ionic conductivity at room temperature and a narrow electrochemical stability window, making it difficult to meet the requirements of high-voltage cathode materials. Simultaneously, the PDOL matrix has insufficient ability to immobilize lithium salt anions, resulting in low lithium-ion transference numbers (typically below 0.5), significant concentration polarization, and uneven electric field distribution on the lithium metal anode surface, which in turn induces lithium dendrite growth. Summary of the Invention

[0004] The purpose of this disclosure is to provide a solid electrolyte, a method for preparing a solid electrolyte, and a solid battery to address the shortcomings of related technologies.

[0005] According to a first aspect of the present disclosure, a solid electrolyte is provided, the solid electrolyte comprising the following components in parts by weight: 65-85 parts by weight of poly(1,3-dioxolane) polymer matrix, 12-25 parts by weight of lithium salt, 0.2-2 parts by weight of first metal-organic framework filler, 0.2-2 parts by weight of inorganic solid electrolyte particles, 0-3 parts by weight of inorganic additives and 0-5 parts by weight of organic additives.

[0006] In one aspect of this disclosure, preferably, the solid electrolyte comprises the following components in parts by weight: 70-80 parts by weight of poly(1,3-dioxolane) polymer matrix, 20-25 parts by weight of lithium salt, 0.3-0.8 parts by weight of first metal-organic framework filler, and 0.25-0.5 parts by weight of inorganic solid electrolyte particles.

[0007] In one aspect of this disclosure, the inorganic solid electrolyte particles are selected from one or more of lithium lanthanum zirconium tantalum oxide (LLZTO), lithium titanium aluminum phosphate (LATP), and lithium lanthanum titanium oxide (LLTO); preferably, the inorganic solid electrolyte particles are selected from lithium lanthanum zirconium tantalum oxide (LLZTO).

[0008] In one aspect of the embodiments of this disclosure, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalateborate), and lithium difluorooxalateborate; preferably, the lithium salt is selected from lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, or lithium difluorooxalateborate; more preferably, the lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide.

[0009] In one aspect of this disclosure, the inorganic additive is selected from one or more of lithium nitrate, alumina nanoparticles, and zirconium oxide nanoparticles.

[0010] In one aspect of this disclosure, the organic additive is selected from one or more of fluoroethylene carbonate, vinylene carbonate, triethyl phosphate, 1,3-dioxane, tri(2,2,2-trifluoroethyl) phosphate, and polyethylene glycol dimethyl ether.

[0011] In one aspect of this disclosure, the first metal-organic framework filler is prepared by the following steps: Step 1-a: Add 2,5-diaminoterephthalic acid to the first organic mixed solution and stir at room temperature until completely dissolved to obtain the solution of step 1-a; wherein, the first organic mixed solution contains ethanol, ethylene glycol and / or propylene glycol; Step 2-a: Add nickel nitrate hexahydrate and cobalt nitrate hexahydrate to the solution from step 1-a, and stir at room temperature until completely dissolved; then add glacial acetic acid dropwise, and continue stirring for 5-15 minutes to obtain the solution from step 2-a; Step 3-a: Transfer the solution from step 2-a to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, seal it, and place it in an oven at 115°C-125°C for 20-30 hours. After the reaction is complete, allow it to cool naturally to room temperature and collect the resulting solid product. Step 4-a: The collected solid product is washed and dried to obtain the first metal-organic framework filler.

[0012] In one aspect of this disclosure, preferably, the first metal-organic framework filler is prepared by the following steps: Step 1-a: Add 0.724 g of 2,5-diaminoterephthalic acid to the first organic mixed solution and stir at room temperature until completely dissolved to obtain the solution of step 1-a; wherein, the first organic mixed solution is obtained by mixing 50 mL of ethanol and 20 mL of ethylene glycol; Step 2-a: Add 0.58 g of nickel nitrate hexahydrate and 1.164 g of cobalt nitrate hexahydrate to the solution from Step 1-a, and stir until completely dissolved at room temperature; then add 1.0 mL of glacial acetic acid dropwise, and continue stirring for 5-10 min to obtain the solution from Step 2-a; Step 3-a: Add the solution from step 2-a to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, seal it, and place it in an oven at 119°C-122°C for 22-25 hours. After the reaction is complete, allow it to cool naturally to room temperature and collect the resulting solid product. Step 4-a: The collected solid product is washed once with ethanol, twice with deionized water, and once more with ethanol. Then it is dried in a vacuum drying oven at 60℃-80℃ for 24-48 hours to obtain the first metal-organic framework filler.

[0013] According to a second aspect of the present disclosure, a method for preparing the aforementioned solid electrolyte is provided, the method comprising the following steps: Step 1: Preparation of the first metal-organic framework filler; Step 2: In an argon atmosphere glove box, dissolve lithium salt in 1,3-dioxolane to obtain solution A; then add the first metal-organic framework filler and inorganic solid electrolyte particles prepared in step 1, stir at room temperature for 2-4 hours, and then ultrasonically disperse for 30-60 minutes to make the first metal-organic framework filler and inorganic solid electrolyte particles uniformly dispersed to obtain the precursor of step 2. Step 3: Dissolve the initiator in the second organic solution to obtain the initiator solution; Step 4: In an argon atmosphere glove box, add the initiator solution obtained in step 3 dropwise to the precursor in step 2, and stir at room temperature for 10-30 min; then let the mixed solution stand and carry out in-situ ring-opening polymerization at room temperature for 12-48 h; Step 5: Allow the reacted system to stand for 12-24 hours to mature, and obtain the solid electrolyte.

[0014] In one aspect of this disclosure, the concentration of lithium salt in solution A is selected from 0.75-1.5 mol / L; specifically, the concentration of lithium salt in solution A is 1.0 mol / L.

[0015] In one aspect of this disclosure, the initiator is selected from aluminum trifluoromethanesulfonate, scandium trifluoromethanesulfonate, zinc trifluoromethanesulfonate, indium trifluoromethanesulfonate, or tin tetrachloride; preferably, the initiator is indium trifluoromethanesulfonate.

[0016] In one aspect of the embodiments of this disclosure, the second organic solution is selected from diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl carbonate, or diethyl carbonate; preferably, the second organic solution is selected from diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, or 1,2-dimethoxyethane; more preferably, the second organic solution is 1,2-dimethoxyethane.

[0017] In one aspect of the present disclosure, the volume ratio of 1,3-dioxolane used in step 2 to the second organic solution used in step 4 is selected from (45-120):1.

[0018] In one aspect of this disclosure, the concentration of the initiator in the initiator solution is selected from 0.05-0.15 mol / L.

[0019] In one aspect of this disclosure, preferably, the method includes the following steps: Step 1: Preparation of the first metal-organic framework filler; Step 2: In an argon-atmosphere glove box, lithium bis(trifluoromethanesulfonyl)imide is dissolved in 1,3-dioxolane to obtain a solution A with a concentration of 1 mol / L. Then, the first metal-organic framework filler and inorganic solid electrolyte particles prepared in Step 1 are added, and the mixture is stirred at room temperature for 2-4 hours, followed by ultrasonic dispersion for 30-60 minutes to ensure uniform dispersion of the first metal-organic framework filler and inorganic solid electrolyte particles, thus obtaining the precursor of Step 2. The mass ratio of the first metal-organic framework filler to the 1,3-dioxolane is selected from (0.2-3.1):100; the mass ratio of the inorganic solid electrolyte particles to the 1,3-dioxolane is selected from (0.2-3.1):100. Step 3: Dissolve indium trifluoromethanesulfonate in 1,2-dimethoxyethane to prepare an initiator solution with a concentration of 0.05-0.15 mol / L; Step 4: In an argon atmosphere glove box, add the initiator solution obtained in step 3 dropwise to the precursor in step 2, stir at room temperature for 10-30 min to homogenize the system; then let the mixed solution stand and carry out in-situ ring-opening polymerization at room temperature for 24-36 h. Step 5: Allow the reacted system to stand for 12-24 hours to mature, and obtain the solid electrolyte.

[0020] According to a third aspect of the present disclosure, a solid-state battery is provided, the solid-state battery comprising a positive electrode, a negative electrode, and the aforementioned solid electrolyte.

[0021] Compared with the prior art, the beneficial effects of this disclosure are: this disclosure prepares a solid electrolyte with good ionic conductivity and improved cycle retention of solid-state batteries. Attached Figure Description

[0022] Figure 1 This is a SEM image of the sheet-like stacked MOF nanomaterials prepared in Example 1 of this disclosure; Figure 2 This is a SEM image of the sheet-like MOF nanomaterial prepared in Example 2 of this disclosure. Detailed Implementation

[0023] Exemplary embodiments will now be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this disclosure. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this disclosure as detailed in the appended claims.

[0024] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. The embodiments described herein are illustrative in nature and are used to provide a basic understanding of this application. The embodiments of this application should not be construed as limiting this application.

[0025] For the sake of brevity, this article only discloses a few specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0026] In this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0027] In this description, unless otherwise stated, "above" and "below" include the stated number.

[0028] Unless otherwise stated, the terms used in this disclosure have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values ​​of the parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this disclosure).

[0029] The term "about" is used to describe and indicate small variations. When used in conjunction with an event or situation, the term may refer to examples in which the event or situation occurred precisely or in examples in which the event or situation occurred very approximately. For example, when used in conjunction with numerical values, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. Additionally, quantities, ratios, and other numerical values ​​are sometimes presented in range format herein. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only numerical values ​​explicitly specified as range limits but also all individual numerical values ​​or subranges covered within the range, as if each numerical value and subrange were explicitly specified.

[0030] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0031] In this disclosure, the solid-state battery provided includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, which is selected from one or more of the following: lithium iron phosphate (LiFePO4), lithium nickel cobalt aluminum oxide (NCA), lithium-rich layered oxides (LLOs), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (NCM), lithium manganese oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium manganese iron phosphate, lithium nickel oxide, sodium vanadium phosphate (Na3V2(PO4)3), vanadium pentoxide (V2O5), sodium manganese oxide, sodium ferrous fluorophosphate (Na2FePO4F), potassium molybdate (KMoO2), ferrite, vanadate, Prussian blue, etc.

[0032] In this disclosure, no particular limitation is made on the preparation method of the positive electrode sheet. In some specific embodiments, it can be prepared by the following method: grinding and mixing 50%-90% by mass of positive active material and 5%-30% by mass of conductive agent, adding 1%-15% by mass of binder and viscosity modifier and grinding and mixing to obtain positive electrode material; then coating the positive electrode material onto the surface of aluminum foil and vacuum drying to obtain positive electrode sheet.

[0033] In this disclosure, the solid-state battery provided includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, which is selected from one or more of the following: lithium metal, lithium metal alloy, carbon silicon composite material, lithium titanate, graphite, lithium metal nitride, antimony oxide, carbon germanium composite material, lithium titanium oxide, sodium metal, sodium metal alloy, hard carbon, soft carbon, titanate, potassium metal, potassium metal alloy, styrene, etc.

[0034] In this disclosure, no particular limitation is placed on the preparation method of the negative electrode sheet. In some specific embodiments, it can be prepared by the following method: grinding and mixing 35%-85% by mass of negative electrode active material and 5%-30% by mass of conductive agent; adding 5%-20% by mass of binder and viscosity modifier and grinding and mixing to obtain negative electrode material; coating the negative electrode material on the surface of copper foil and drying to obtain negative electrode sheet.

[0035] In this disclosure, there is no particular limitation on the types of conductive agents, binders, and viscosity modifiers used in the positive and negative electrode materials. Those commonly used in the art can be selected. For example, the conductive agent may include one or more of conductive graphite, graphene, acetylene black, carbon black Super P, carbon nanotubes, etc.; the binder may include polyvinylidene fluoride (PVDF), etc.; the viscosity modifier may include one or more of N-methylpyrrolidone (NMP), 1-methyl-2-pyrrolidone, etc., wherein the viscosity modifier is used to adjust the viscosity and is not included in the mass percentage composition of the positive / negative electrode materials.

[0036] The present disclosure will be further described below by way of specific embodiments. Unless otherwise specified, all chemical reagents used in the embodiments of the present disclosure are obtained through conventional commercial means. Unless otherwise specified, all contents mentioned below are mass contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.

[0037] Examples and comparative examples.

[0038] Example 1

[0039] Example 1 includes the following steps: 1. Preparation of the metal-organic framework filler of this embodiment: 0.724 g of 2,5-diaminoterephthalic acid was added to a mixed solution of 50 mL anhydrous ethanol and 20 mL ethylene glycol. The solution was magnetically stirred for 30 min at room temperature until completely dissolved, yielding a solution. 0.58 g of nickel nitrate hexahydrate and 1.164 g of cobalt nitrate hexahydrate were added sequentially to the above solution, and the mixture was magnetically stirred for 30 min at room temperature until the metal salts were completely dissolved. Then, 1.0 mL of glacial acetic acid was added dropwise, and stirring was continued for 10 min, yielding a solution. The resulting solution was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, sealed, and heated in a 120°C oven for 24 h. After the reaction was complete, the oven power was turned off, and the reactor was allowed to cool naturally to room temperature. The resulting solid product was collected. The collected solid product was washed once with anhydrous ethanol, twice with deionized water, and once more with anhydrous ethanol, each centrifugation at 4000 rpm for 5 min. After washing, the product was dried in an 80°C vacuum oven for 24 h to obtain layered stacked MOF nanomaterials. These nanomaterials were then ground and transferred to an argon-atmosphere glove box for later use, where the water and oxygen content was below 0.5 ppm. The SEM image of the layered stacked MOF nanomaterials prepared in this embodiment is shown below. Figure 1 As shown.

[0040] 2. Preparation of the solid electrolyte in this embodiment: In an argon-atmosphere glove box, 2.87 g of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 10 mL of 1,3-dioxolane to prepare a solution A with a lithium salt concentration of 1 mol / L. Subsequently, 0.085 g of the aforementioned dried sheet-like stacked MOF nanomaterials and 0.053 g of nano-sized lithium lanthanum zirconium tantalum oxide powder (average particle size of about 500 nm) were added to solution A. The mixture was magnetically stirred at room temperature for 3 h and then ultrasonically dispersed for 30 min to ensure that the sheet-like stacked MOF nanomaterials and lithium lanthanum zirconium tantalum oxide particles were uniformly dispersed in the monomer solution, thus obtaining a liquid precursor.

[0041] In an argon-atmospheric glove box, indium trifluoromethanesulfonate was dissolved in 0.2 mL of 1,2-dimethoxyethane to prepare an initiator solution with a concentration of 0.1 mol / L.

[0042] In an argon-atmospheric glove box, the obtained initiator solution was slowly added dropwise to the precursor, and the system was magnetically stirred for 15 minutes at room temperature to homogenize it. Subsequently, the mixed solution was divided into two portions: one portion was poured into a polytetrafluoroethylene flat-bottomed mold, placed horizontally, and subjected to in-situ ring-opening polymerization at room temperature for 24 hours. The 1,3-dioxolane monomer polymerized into poly(1,3-dioxolane) long chains, and the layered stacked MOF nanomaterials and lithium lanthanum zirconium tantalum oxide particles were uniformly embedded in the polymer matrix to obtain a solid electrolyte. The solid electrolyte was further allowed to stand and mature in an argon atmosphere for 12 hours, and then cut into discs with a diameter of 16 mm for electrochemical performance testing.

[0043] 3. Preparation of the solid-state battery in this embodiment: Preparation of the positive electrode sheet: Sulfur powder and Ketjen black were ground and mixed evenly at a mass ratio of 7:3, and then heat-treated in a tube furnace at 155°C for 12 hours to obtain a sulfur-Ketjen black composite positive electrode material. The sulfur-Ketjen black composite material was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 8:1:1 in N-methylpyrrolidone and stirred for 24 hours to obtain a positive electrode slurry. The positive electrode slurry was coated onto an aluminum foil current collector and vacuum dried at 60°C for 12 hours to obtain a sulfur positive electrode sheet.

[0044] Solid-state battery assembly: In an argon-atmospheric glove box, a small amount of the remaining precursor solution was dropped onto the surface of a polypropylene membrane (Celgard 2400). Then, sulfur positive electrode, polypropylene membrane containing mixed solution, and lithium metal negative electrode were stacked in sequence to assemble a CR2032 type button cell. The assembled battery was left to stand at room temperature for 24 hours to allow the precursor solution to complete in-situ ring-opening polymerization. After standing for 12 hours, the Li-S solid-state battery of this embodiment was obtained.

[0045] Example 2

[0046] Example 2 includes the following steps: 1. Preparation of the metal-organic framework filler of this embodiment: 0.724 g of 2,5-diaminoterephthalic acid was added to a mixed solution consisting of 45 mL of anhydrous ethanol and 15 mL of deionized water. The solution was magnetically stirred for 30 min at room temperature until completely dissolved. Then, 0.58 g of nickel nitrate hexahydrate and 1.164 g of cobalt nitrate hexahydrate were added sequentially to the above solution. The mixture was magnetically stirred for 30 min at room temperature until the metal salts were completely dissolved. The resulting solution was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, sealed, and heated in a 120°C oven for 24 h. After the reaction was complete, the oven power was turned off, and the reactor was allowed to cool naturally to room temperature. The resulting solid product was collected. The collected solid product was washed sequentially by centrifugation once with anhydrous ethanol, twice with deionized water, and once more with anhydrous ethanol. Each centrifugation was performed at 4000 rpm for 5 minutes. After washing, the product was dried in a vacuum drying oven at 80°C for 24 hours to obtain the layered MOF nanomaterials of this embodiment. These nanomaterials were then ground and transferred to an argon-atmosphere glove box for later use. The water and oxygen content in the glove box was below 0.5 ppm. The SEM image of the layered MOF nanomaterials prepared in this embodiment is shown below. Figure 2 As shown.

[0047] 2. Preparation of the solid electrolyte in this embodiment: In an argon-atmosphere glove box, 2.87 g of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 10 mL of 1,3-dioxolane to prepare a solution A with a lithium salt concentration of 1 mol / L. Subsequently, 0.085 g of the aforementioned dried layered MOF nanomaterials and 0.053 g of nano-sized lithium lanthanum zirconium tantalum oxide powder (average particle size of about 500 nm) were added to solution A. The mixture was magnetically stirred at room temperature for 3 h and then ultrasonically dispersed for 30 min to ensure that the layered MOF nanomaterials and lithium lanthanum zirconium tantalum oxide particles were uniformly dispersed in the monomer solution, thus obtaining a liquid precursor.

[0048] In an argon-atmospheric glove box, indium trifluoromethanesulfonate was dissolved in 0.2 mL of 1,2-dimethoxyethane to prepare an initiator solution with a concentration of 0.1 mol / L.

[0049] In an argon-atmospheric glove box, the obtained initiator solution was slowly added dropwise to the precursor, and the system was magnetically stirred for 15 minutes at room temperature to homogenize it. Subsequently, the mixed solution was divided into two portions: one portion was poured into a polytetrafluoroethylene flat-bottomed mold, placed horizontally, and subjected to in-situ ring-opening polymerization at room temperature for 24 hours. The 1,3-dioxolane monomer polymerized into poly(1,3-dioxolane) long chains, and the layered MOF nanomaterials and lithium lanthanum zirconium tantalum oxide particles were uniformly embedded in the polymer matrix to obtain a solid electrolyte. The solid electrolyte was further allowed to stand and mature in an argon atmosphere for 12 hours, and then cut into discs with a diameter of 16 mm for electrochemical performance testing.

[0050] 3. Preparation of the solid-state battery in this embodiment: Preparation of the positive electrode sheet: Sulfur powder and Ketjen black were ground and mixed evenly at a mass ratio of 7:3, and then heat-treated in a tube furnace at 155°C for 12 hours to obtain a sulfur-Ketjen black composite positive electrode material. The sulfur-Ketjen black composite material was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 8:1:1 in N-methylpyrrolidone and stirred for 24 hours to obtain a positive electrode slurry. The positive electrode slurry was coated onto an aluminum foil current collector and vacuum dried at 60°C for 12 hours to obtain a sulfur positive electrode sheet.

[0051] Solid-state battery assembly: In an argon-atmospheric glove box, a small amount of the remaining precursor solution was dropped onto the surface of a polypropylene membrane (Celgard 2400). Then, sulfur positive electrode, polypropylene membrane containing mixed solution, and lithium metal negative electrode were stacked in sequence to assemble a CR2032 type button cell. The assembled battery was left to stand at room temperature for 24 hours to allow the precursor solution to complete in-situ ring-opening polymerization. After standing for 12 hours, the Li-S solid-state battery of this embodiment was obtained.

[0052] Example 3

[0053] Example 3 includes the following steps: 1. Preparation of the metal-organic framework filler of this embodiment: 1.67 g of 3,5-pyridinedicarboxylic acid was added to 100 mL of deionized water and magnetically stirred at room temperature until completely dissolved to obtain a solution. 1.19 g of cobalt chloride hexahydrate and 0.76 g of nickel chloride hexahydrate were added to the above solution and stirred at room temperature for 30 min until completely dissolved. Then, potassium hydroxide solution was added dropwise to adjust the pH to approximately 7.5, and stirring was continued for 10 min to obtain a solution. The solution was allowed to stand, and the reaction was allowed to proceed at room temperature to form a precipitate. After the reaction was complete, the obtained solid product was collected by filtration. The collected solid product was washed sequentially with ethanol, deionized water, and then ethanol again, and then dried in a 60°C oven for 12 h to obtain the bimetallic MOF material of this embodiment. After grinding, it was transferred to an argon-atmosphere glove box for later use, where the water and oxygen content were both below 0.5 ppm.

[0054] 2. Preparation of the solid electrolyte in this embodiment: The preparation process in Example 3 is basically the same as that in Example 1, except that the bimetallic MOF material prepared above is used instead of the sheet-stacked MOF nanomaterial prepared in Example 1.

[0055] 3. Preparation of the solid-state battery in this embodiment: The preparation process in Example 3 is basically the same as that in Example 1, except that the solid electrolyte prepared above is used instead of the solid electrolyte prepared in Example 1.

[0056] Example 4

[0057] Example 4 includes the following steps: 1. Preparation of the metal-organic framework filler of this embodiment: 3.93 g of 4,4'-biphenyl dicarboxylic acid and 470 mg of 4,4'-biphenyl dicarboxylic acid were added to 250 mL of N,N-dimethylformamide and magnetically stirred at room temperature until completely dissolved to obtain a solution. 4.5 g of zirconium tetrachloride was added to the above solution and stirred at room temperature until completely dissolved; then 5.0 mL of glacial acetic acid was added dropwise, and stirring was continued for 10 min to obtain a solution. The solution was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, sealed, and heated in a 120°C oven for 16 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the resulting solid product was collected by centrifugation. The collected solid product was washed three times by centrifugation with N,N-dimethylformamide, then soaked in methanol for 36 h, with the methanol being replaced every 12 h; subsequently, it was removed, dried, and placed in a 60°C vacuum drying oven for 12 h to obtain UiO-67 nanomaterials. After grinding, the nanomaterials were transferred to an argon-atmosphere glove box for later use, where the water and oxygen content was below 0.5 ppm.

[0058] 2. Preparation of the solid electrolyte in this embodiment: The preparation process in Example 4 is basically the same as that in Example 1, except that the UiO-67 nanomaterial prepared above is used instead of the sheet-stacked MOF nanomaterial prepared in Example 1.

[0059] 3. Preparation of the solid-state battery in this embodiment: The preparation process in Example 4 is basically the same as that in Example 1, except that the solid electrolyte prepared above is used instead of the solid electrolyte prepared in Example 1.

[0060] Example 5

[0061] Example 5 includes the following steps: 1. Preparation of the metal-organic framework filler of this embodiment: 1.64 g of 2-methylimidazole was added to 100 mL of methanol and magnetically stirred at room temperature until completely dissolved to obtain a solution. 2.97 g of zinc nitrate hexahydrate was added to the above solution and stirred at room temperature for 30 min until completely dissolved to obtain a solution. The solution was allowed to stand at room temperature for 24 h to form a precipitate. After the reaction was complete, the solid product was collected by centrifugation. The collected solid product was washed three times by centrifugation with methanol and then dried in an 80°C vacuum drying oven for 12 h to obtain ZIF-8 particulate material. After grinding, it was transferred to an argon-atmosphere glove box for later use, where the water and oxygen content were both below 0.5 ppm.

[0062] 2. Preparation of the solid electrolyte in this embodiment: The preparation process in Example 5 is basically the same as that in Example 1, except that the ZIF-8 particles prepared above are used instead of the sheet-stacked MOF nanomaterials prepared in Example 1.

[0063] 3. Preparation of the solid-state battery in this embodiment: The preparation process in Example 5 is basically the same as that in Example 1, except that the solid electrolyte prepared above is used instead of the solid electrolyte prepared in Example 1.

[0064] Example 6 Example 6 includes the following steps: 1. Preparation of the metal-organic framework filler of this embodiment: 1.64 g of 2-methylimidazole was added to 100 mL of methanol and magnetically stirred at room temperature until completely dissolved to obtain a solution. 2.91 g of cobalt nitrate hexahydrate was added to the above solution and stirred at room temperature for 30 min until completely dissolved to obtain a solution. The solution was allowed to stand at room temperature for 24 h to form a precipitate. After the reaction was complete, the solid product was collected by centrifugation. The collected solid product was washed three times by centrifugation with methanol and then dried in an 80°C vacuum drying oven for 12 h to obtain ZIF-67 particulate material. After grinding, it was transferred to an argon-atmosphere glove box for later use, where the water and oxygen content were both below 0.5 ppm.

[0065] 2. Preparation of the solid electrolyte in this embodiment: The preparation process in Example 6 is basically the same as that in Example 1, except that the ZIF-67 particles prepared above are used instead of the sheet-stacked MOF nanomaterials prepared in Example 1.

[0066] 3. Preparation of the solid-state battery in this embodiment: The preparation process in Example 6 is basically the same as that in Example 1, except that the solid electrolyte prepared above is used instead of the solid electrolyte prepared in Example 1.

[0067] Comparative Example 1 Comparative Example 1 includes the following steps: 1. Preparation of the solid electrolyte of this comparative example: In an argon-atmosphere glove box, 2.87 g of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 10 mL of 1,3-dioxolane to prepare a solution A with a lithium salt concentration of 1 mol / L. Then, 0.053 g of nano-sized lithium lanthanum zirconium tantalum oxide powder (average particle size of about 500 nm) was added to solution A, and the mixture was magnetically stirred at room temperature for 3 h, followed by ultrasonic dispersion for 30 min, so that the lithium lanthanum zirconium tantalum oxide particles were uniformly dispersed in the monomer solution to obtain a liquid precursor.

[0068] In an argon-atmospheric glove box, indium trifluoromethanesulfonate was dissolved in 0.2 mL of 1,2-dimethoxyethane to prepare an initiator solution with a concentration of 0.1 mol / L.

[0069] In an argon-atmospheric glove box, the obtained initiator solution was slowly added dropwise to the precursor, and the system was magnetically stirred for 15 minutes at room temperature to homogenize it. The mixed solution was then divided into two portions: one portion was poured into a polytetrafluoroethylene flat-bottomed mold, placed horizontally, and subjected to in-situ ring-opening polymerization at room temperature for 24 hours. The 1,3-dioxolane monomer polymerized into a poly(1,3-dioxolane) long chain, and lithium lanthanum zirconium tantalum oxide particles were uniformly embedded in the polymer matrix to obtain a solid electrolyte. This solid electrolyte was further cured in an argon atmosphere for 12 hours, then cut into 16 mm diameter discs for electrochemical performance testing.

[0070] 2. Preparation of the solid-state battery of this comparative example: Preparation of the positive electrode sheet: Sulfur powder and Ketjen black were ground and mixed evenly at a mass ratio of 7:3, and then heat-treated in a tube furnace at 155°C for 12 hours to obtain a sulfur-Ketjen black composite positive electrode material. The sulfur-Ketjen black composite material was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 8:1:1 in N-methylpyrrolidone and stirred for 24 hours to obtain a positive electrode slurry. The positive electrode slurry was coated onto an aluminum foil current collector and vacuum dried at 60°C for 12 hours to obtain a sulfur positive electrode sheet.

[0071] Solid-state battery assembly: In an argon-atmospheric glove box, a small amount of the remaining precursor solution was dropped onto the surface of a polypropylene membrane (Celgard 2400). Then, sulfur positive electrode, polypropylene membrane containing mixed solution, and lithium metal negative electrode were stacked in sequence to assemble a CR2032 type button cell. The assembled cell was left to stand at room temperature for 24 hours to allow the precursor solution to complete in-situ ring-opening polymerization. After standing for 12 hours, the Li-S solid-state battery of this comparative example was obtained.

[0072] Performance testing: Ionic conductivity (σ) test: The solid electrolytes obtained in each embodiment and comparative example were cut into 16mm diameter discs and sandwiched between two stainless steel discs to assemble a symmetrical battery. Electrochemical impedance spectroscopy (EIS) was used on an electrochemical workstation with a frequency range of 100mHz-1MHz, an AC voltage amplitude of 10mV, and a test temperature of 30°C. The electrolyte thickness D was measured using an inductive thickness gauge, and the effective contact area of ​​the stainless steel electrode was denoted as S. The ionic conductivity was calculated using the formula σ=D / (R×S), where R is the resistance at the intersection of the high-frequency semicircle and the real axis in the EIS spectrum. The results are shown in Table 1.

[0073] Lithium-ion transference number (t_Li) + )test The solid electrolytes obtained in each embodiment and comparative example were cut into 16mm diameter discs and sandwiched between two lithium metal discs to assemble a symmetrical battery. A DC polarization voltage ΔV = 10mV was applied to an electrochemical workstation, and the initial current I0 and steady-state current I were recorded. s Simultaneously, EIS tests were performed before and after polarization, and the resistance R0 before polarization and the resistance R after polarization were recorded. s The lithium-ion transport number is expressed by the formula t_Li. + =I s (ΔV-I0R0) / [I0(ΔV−I s R s )]calculate.

[0074] Li-S full cell cycle performance test: The Li-S solid-state batteries assembled in each embodiment and comparative example were subjected to constant current charge-discharge tests on a battery testing system, with a voltage window of 1.7-2.8V (vs. Li). + / Li) Current density 0.16 mA / cm 2 The test temperature was 30°C. The initial discharge specific capacity, discharge specific capacity after 250 cycles, and capacity retention were recorded. The results are shown in Table 1.

[0075]

[0076] The ionic conductivity and cycling capacity retention of Example 1 are significantly better than those of other comparative examples and examples. This is because the face-to-face oriented stacked structure of the prepared sheet-like MOF-NH2 constructs a low-torsion oriented ion channel in the PDOL matrix. Simultaneously, the Ni / Co bimetallic Lewis acid sites and amino groups synergistically promote lithium salt dissociation and anion fixation. Example 2 differs slightly from Example 1 in the preparation steps of the MOF-NH2 material. The obtained MOF-NH2 material is sheet-like instead of the sheet-like stacked structure of Example 1, and the stacking density is lower than that of Example 1. Therefore, the ionic conductivity and cycling capacity retention are significantly lower. Although the Ni / Co pyridine dicarboxylic acid MOF of Example 3 contains Ni / Co bimetal, it lacks amino functional groups and cannot form oriented ion channels, resulting in significantly inferior performance compared to Example 1. Examples 5 (ZIF-8) and 6 (ZIF-67) are Zn-based and Co-based ZIF materials, respectively. They have neither amino groups nor layered stacked structures. Furthermore, the hydrophobic channels of ZIF physically block the movement of PDOL chain segments, resulting in lower ionic conductivity than Comparative Example 1 without MOF materials. The Li-S cycling also suffers from severe degradation.

[0077] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary; within the framework of this invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

[0078] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A solid electrolyte, characterized in that, The solid electrolyte comprises the following components in parts by weight: 65-85 parts by weight of poly(1,3-dioxolane) polymer matrix, 12-25 parts by weight of lithium salt, 0.2-2 parts by weight of first metal-organic framework filler, 0.2-2 parts by weight of inorganic solid electrolyte particles, 0-3 parts by weight of inorganic additives and 0-5 parts by weight of organic additives.

2. The solid electrolyte according to claim 1, characterized in that, The inorganic solid electrolyte particles are selected from one or more of lithium lanthanum zirconium tantalum oxide, lithium titanium aluminum phosphate, and lithium lanthanum titanium oxide.

3. The solid electrolyte according to claim 1, characterized in that, The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalate-borate), and lithium difluorooxalate-borate.

4. The solid electrolyte according to claim 1, characterized in that, The inorganic additive is selected from one or more of lithium nitrate, alumina nanoparticles, and zirconium oxide nanoparticles. The organic additive is selected from one or more of fluoroethylene carbonate, vinylene carbonate, triethyl phosphate, 1,3-dioxane, tri(2,2,2-trifluoroethyl) phosphate, and polyethylene glycol dimethyl ether.

5. The solid electrolyte according to claim 1, characterized in that, The first metal-organic framework filler is prepared by the following steps: Step 1-a: Add 2,5-diaminoterephthalic acid to the first organic mixed solution and stir at room temperature until completely dissolved to obtain the solution of step 1-a; wherein, the first organic mixed solution contains ethanol, ethylene glycol and / or propylene glycol; Step 2-a: Add nickel nitrate hexahydrate and cobalt nitrate hexahydrate to the solution from step 1-a, and stir at room temperature until completely dissolved; then add glacial acetic acid dropwise, and continue stirring for 5-15 minutes to obtain the solution from step 2-a; Step 3-a: Transfer the solution from step 2-a to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, seal it, and place it in an oven at 115°C-125°C for 20-30 hours. After the reaction is complete, allow it to cool naturally to room temperature and collect the resulting solid product. Step 4-a: The collected solid product is washed and dried to obtain the first metal-organic framework filler.

6. The solid electrolyte according to claim 5, characterized in that, The first metal-organic framework filler is prepared by the following steps: Step 1-a: Add 0.724 g of 2,5-diaminoterephthalic acid to the first organic mixed solution and stir at room temperature until completely dissolved to obtain the solution of step 1-a; wherein, the first organic mixed solution is obtained by mixing 50 mL of ethanol and 20 mL of ethylene glycol; Step 2-a: Add 0.58g of nickel nitrate hexahydrate and 1.164g of cobalt nitrate hexahydrate to the solution from Step 1-a, and stir until completely dissolved at room temperature; then add 1.0mL of glacial acetic acid dropwise, and continue stirring for 5-10 minutes to obtain the solution from Step 2-a; Step 3-a: Transfer the solution from step 2-a to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, seal it, and place it in an oven at 119°C-122°C for 22-25 hours. After the reaction is complete, allow it to cool naturally to room temperature and collect the resulting solid product. Step 4-a: The collected solid product is washed once with ethanol, twice with deionized water, and once more with ethanol. Then it is dried in a vacuum drying oven at 60℃-80℃ for 24-48 hours to obtain the first metal-organic framework filler.

7. A method for preparing the solid electrolyte according to any one of claims 1-6, characterized in that, The method includes the following steps: Step 1: Preparation of the first metal-organic framework filler; Step 2: In an argon atmosphere glove box, dissolve lithium salt in 1,3-dioxolane to obtain solution A; then add the first metal-organic framework filler and inorganic solid electrolyte particles prepared in step 1, stir at room temperature for 2-4 hours, and then ultrasonically disperse for 30-60 minutes to make the first metal-organic framework filler and inorganic solid electrolyte particles uniformly dispersed to obtain the precursor of step 2. Step 3: Dissolve the initiator in the second organic solution to obtain the initiator solution; Step 4: In an argon atmosphere glove box, add the initiator solution obtained in step 3 dropwise to the precursor in step 2, and stir at room temperature for 10-30 min; then let the mixed solution stand and carry out in-situ ring-opening polymerization at room temperature for 12-48 h; Step 5: Allow the reacted system to stand for 12-24 hours to mature, and obtain the solid electrolyte.

8. The method according to claim 7, characterized in that, The method satisfies at least one of the following conditions: (1) In solution A, the concentration of lithium salt is selected from 0.75-1.5 mol / L; (2) The initiator is selected from aluminum trifluoromethanesulfonate, scandium trifluoromethanesulfonate, zinc trifluoromethanesulfonate, indium trifluoromethanesulfonate or tin tetrachloride; (3) The second organic solution is selected from diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl carbonate or diethyl carbonate; (4) The volume ratio of 1,3-dioxolane used in step 2 to the second organic solution used in step 4 is selected from (45-120):1; (5) The concentration of the initiator in the initiator solution is selected from 0.05-0.15 mol / L.

9. The method according to claim 8, characterized in that, The method includes the following steps: Step 1: Preparation of the first metal-organic framework filler; Step 2: In an argon-atmosphere glove box, lithium bis(trifluoromethanesulfonyl)imide is dissolved in 1,3-dioxolane to obtain a solution A with a concentration of 1 mol / L. Then, the first metal-organic framework filler and inorganic solid electrolyte particles prepared in Step 1 are added, and the mixture is stirred at room temperature for 2-4 hours, followed by ultrasonic dispersion for 30-60 minutes to ensure uniform dispersion of the first metal-organic framework filler and inorganic solid electrolyte particles, thus obtaining the precursor of Step 2. The mass ratio of the first metal-organic framework filler to the 1,3-dioxolane is selected from (0.2-3.1):100; the mass ratio of the inorganic solid electrolyte particles to the 1,3-dioxolane is selected from (0.2-3.1):

100. Step 3: Dissolve indium trifluoromethanesulfonate in 1,2-dimethoxyethane to prepare an initiator solution with a concentration of 0.05-0.15 mol / L; Step 4: In an argon atmosphere glove box, add the initiator solution obtained in step 3 dropwise to the precursor in step 2, stir at room temperature for 10-30 min to homogenize the system; then let the mixed solution stand and carry out in-situ ring-opening polymerization at room temperature for 24-36 h. Step 5: Allow the reacted system to stand for 12-24 hours to mature, and obtain the solid electrolyte.

10. A solid-state battery, characterized in that, The solid-state battery comprises a positive electrode, a negative electrode, and a solid electrolyte as described in any one of claims 1-6.